Green approach to corrosion inhibition of mild steel in hydrochloric acid and sulphuric acid solutions by the extract of Murraya koenigii leaves - Quraishi M.A.; Singh A.; Singh V.K.; Yadav D.K.; Singh A.K. (My University, 2025)
The inhibition of the corrosion of mild steel in hydrochloric acid and sulphuric acid solutions by the extract of Murraya koenigii leaves has been studied using weight loss, electrochemical impedance spectroscopy (EIS), linear polarization and potentiodynamic polarization techniques. Inhibition was found to increase with increasing concentration of the leaves extract. The effect of temperature, immersion time and acid concentration on the corrosion behavior of mild steel in 1 M HCl and 0.5 M H2SO4 with addition of extract was also studied. The inhibition was assumed to occur via adsorption of the inhibitor molecules on the metal surface. The adsorption of the extract on the mild steel surface obeys the Langmuir adsorption isotherm. The activation energy as well as other thermodynamic parameters (Q, ΔH*, and ΔS*) for the inhibition process was calculated. These thermodynamic parameters show strong interaction between inhibitor and mild steel surface. The results obtained show that the extract of the leaves of M. koenigii could serve as an effective inhibitor of the corrosion of mild steel in hydrochloric and sulphuric acid media. © 2010 Elsevier B.V. All rights reserved.